Alternative controls in the management of rot by Fusarium sp. in melon post-harvest: a review (Research, Society and Development, 2022)
Melon is a fruit of great economic importance in the Northeast region of Brazil, highly affected by post-harvest diseases, caused by quiescent fungi such as the Fusarium genus. The present review aimed to highlight different alternative managements in the management of post-harvest diseases as an ally in reducing the use of agrochemicals. The narrative review was developed with scientific production indexed in the following electronic databases: Brazilian Digital Library of Theses and Dissertations (BDTD), CAPES, and Google Scholar, using the following keywords: melon, alternative control, post- harvest, Fusarium. The control of phytopathogens in the post-harvest is carried out mainly with agrochemicals that, due to the requirements of the international market, for the reduction or elimination of residues in food, have sought new technologies that can minimize the application of synthetic compounds. Alternative controls such as thermal, coatings and ozonation are already commercially used for the treatment of post-harvest diseases, in which some in the study phase have shown to be efficient and, in the future, joint managements can be carried out in order to maximize the efficiency in the control of post-harvest diseases.